Compound Danshen Dripping Pills pretreatment protects the heart from ischemia/reperfusion injury by enhancing autophagic flux - Haiqiong Liu; Qian Liang; Xiheng Mei; Hekai Li; Jing Yan; Man Long; Xili Yang; Wei Wang; Weijie Li; Aihua Chen; Yuanna Ling (Universidade de São Paulo, 2023)
Abstract Compound Danshen Dripping Pills (CDDPs) have been used in clinical treatment to protect the heart from ischemia/reperfusion (IR) injury for many years. However, the underlying mechanism implicated in the protective effects remains to be explored. Here, we determined the effects of CDDPs in Sprague-Dawley rats with the IR model. Cardiac function in vivo was assessed by echocardiography. Transmission electron microscopy, histological and immunohistochemical techniques, Western blotting and recombinant adeno-associated virus 9 transfection were used to illustrate the effects of CDDPs on IR and autophagy. Our results showed that pretreatment with CDDPs decreased the level of serum myocardial enzymes and infarct size in rats after IR. Apoptosis evaluation showed that CDDPs significantly ameliorated the cardiac apoptosis level after IR. Meanwhile, CDDPs pretreatment increased myocardial autophagic flux, with upregulation of LC3B, downregulation of p62, and increased autophagosomes and autolysosomes. Moreover, the autophagic flux inhibitor chloroquine could increase IR injury, while CDDPs could partially reverse the effects. Furthermore, our results showed that the activation of AMPK/mTOR was involved in the cardioprotective effect exerted by CDDPs. Herein, we suggest that CDDPs partially protect the heart from IR injury by enhancing autophagic flux through the activation of AMPK/mTOR.